2019
DOI: 10.7150/jca.30789
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of BRAFV600E Mutation in Colorectal Cancer: An Updated Meta-Analysis

Abstract: Background and Aims: Numerous studies have identified BRAF V600E mutation as a predictive factor of anti-EGFR antibodies in colorectal cancer (CRC). However, the association between BRAF V600E mutation and clinicopathological features remains unclear. Therefore, we aimed to conduct an updated and comprehensive meta-analysis to evaluate the above issues. Methods: We performed a systematic literature search from PubMed, Web of Science, Embase, and PMC database examining the association between BRAF V600E mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 72 publications
4
23
1
Order By: Relevance
“…The four patients bearing the p.V600E variant were three women and a man, all older than 60 years, with tumors located in the proximal colon, three of which were at stages III–IV. Although no statistical approach was possible due to the low number of patients positive for the pathogenic variant, the characteristics of these subjects are in agreement with the clinicopathological features associated with BRAF p.V600E described in three meta-analyses 12–14. Chen et al 12 reported an analysis of 25 studies, published before 2013, and estimated a frequency of this pathogenic variant of 10.8% among 11,955 patients with CRC.…”
Section: Discussionsupporting
confidence: 58%
“…The four patients bearing the p.V600E variant were three women and a man, all older than 60 years, with tumors located in the proximal colon, three of which were at stages III–IV. Although no statistical approach was possible due to the low number of patients positive for the pathogenic variant, the characteristics of these subjects are in agreement with the clinicopathological features associated with BRAF p.V600E described in three meta-analyses 12–14. Chen et al 12 reported an analysis of 25 studies, published before 2013, and estimated a frequency of this pathogenic variant of 10.8% among 11,955 patients with CRC.…”
Section: Discussionsupporting
confidence: 58%
“…In fact, as emerged in a recent meta-analysis [14], BRAF V600E-mutated tumors more commonly arise from serrated adenomas, mainly in the right colon, with a higher incidence in women and elderly patients (age >60-years-old). Moreover, BRAF V600E-mutated CRCs are often poorly differentiated and present a mucinous histotype.…”
Section: Clinical Data On Braf V600e- and Non-v600-mutated Crcmentioning
confidence: 99%
“…Molecular profiling for various mutations, namely BRAF and RAS, as well as for microsatellite instability (MSI) is critical for treatment decisions. In particular, the presence of the BRAF V600E mutation, which is seen in approximately 10% of mCRC, is associated with a worse prognosis [3]. BRAF V600E mut mCRC exhibits unique clinicopathological features including older age and higher stage at diagnosis, predilection for females, right-sided tumor location, poor differentiation, and MSI-high phenotype [3,4].…”
Section: Introductionmentioning
confidence: 99%